The key role of insulin-like growth factor I in limbal stem cell differentiation and the corneal wound-healing process - Trosan, Peter; Svobodova, Eliska; Chudickova, Milada; Krulova, Magdalena; Zajicova, Alena; Holan, Vladimir (Stem cells and development, 2012)
Limbal stem cells (LSC), which reside in the basal layer of the limbus, are thought to be responsible for corneal epithelial healing after injury. When the cornea is damaged, LSC start to proliferate, differentiate, and migrate to the site of injury. To characterize the signaling molecules ensuring communication between the cornea and LSC, we established a mouse model of mechanical corneal damage. The central cornea or limbal tissue was excised at different time intervals after injury, and the expression of genes in the explants was determined. It was observed that a number of genes for growth and differentiation factors were significantly upregulated in the cornea rapidly after injury. The ability of these factors to regulate the differentiation and proliferation of limbal cells was tested. It was found that the insulin-like growth factor-I (IGF-I), which is rapidly overexpressed after injury, enhances the expression of IGF receptor in limbal cells and induces the differentiation of LSC into cells expressing the corneal cell marker, cytokeratin K12, without any effect on limbal cell proliferation. In contrast, the epidermal growth factor (EGF) and fibroblast growth factor-β (FGF-β), which are also produced by the damaged corneal epithelium, supported limbal cell proliferation without any effect on their differentiation. Other factors did not affect limbal cell differentiation or proliferation. Thus, IGF-I was identified as the main factor stimulating the expression of IGF receptors in limbal cells and inducing the differentiation of LSC into cells expressing corneal epithelial cell markers. The proliferation of these cells was supported by EGF and FGF.
Keywords: epidermální růstový faktor; Male; Up-Regulation; Cell Proliferation; fibroblastové růstové faktory; receptor IGF typ 1; Epithelium, Corneal; Insulin-Like Growth Factor I; signální transdukce; buněčná diferenciace; myši inbrední BALB C; upregulace; Keratin-12; mužské pohlaví; Epidermal Growth Factor; stanovení celkové genové exprese; Signal Transduction; Mice, Inbred BALB C; Gene Expression Profiling; Limbus Corneae; Stem Cells; insulinu podobný růstový faktor I; Animals; keratin-12; Receptor, IGF Type 1; Wound Healing; ženské pohlaví; Fibroblast Growth Factors; zvířata; myši; proliferace buněk; Mice; Female; kmenové buňky; limbus corneae; Cell Differentiation; hojení ran; rohovkový epitel